Research on deep differential fault analysis against MIBS - ZHAO Xin-jie1; WANG Tao 1; WANG Su-zhen2; WU Yang1 (Tongxin xuebao)
The MIBS algorithm and its differential fault analysis principle were presented,then three differential fault analysis methods against MIBS were proposed based on different depth of fault model and verified through experiments.Experiment results demonstrate that due to its Feistel structure and S-box differential feature,MIBS is vulnerable to deep differential fault attack.The best result is that after injecting one 4-bit fault into the 30th round left register,both the fault location and fault differential are unknown,the 64-bit MIBS master key searching space can be reduced to 224 and be re-covered after one minute brute-force-search.Moreover,the fault analysis method can provide some ideas on differential fault analysis against other block ciphers using S-box.